Is Higher-Order Misrepresentation Empirically Plausible? An Argument From Corruption - Kirkeby-Hinrup, Asger (Frontiers in Psychology, 2022)
I present an empirically based argument for the plausibility of misrepresentation as posited by some higher-order theories of consciousness. The argument relies on the assumption that conscious states are generated by processes in the brain. The underlying idea is that if the brain generates conscious states then misrepresentation may occur. The reason for this is that brain states can be corrupted and, accordingly, a conscious state that is at least partly caused by a corrupted brain state may be a misrepresentation. Our body of knowledge from cognitive and behavioral neuroscience lends support to the idea that corruption of neural states is both possible and relatively frequent. If this is the case, I argue, it is plausible that occasionally such corruption may result in misrepresentation. I support this claim by arguing that the most prevalent theoretical alternative to the occurrence of misrepresentation — the so-called no-consciousness reply — seems less supported by our current knowledge in the domain of consciousness and cognition. This way of arguing for misrepresentation is different from other empirically based arguments in the debate because it is a meta-level argument resting on a general premise that most participants in the debate can accept.